Ethnic landscapes in an urban world - Hutchison, Ray.; Krase, Jerome (Amsterdam ; Oxford : Elsevier JAI, 2007)
This series addresses the major subject areas of urban sociology, ethnic and minority groups within the city, social network of urban residents, location of retail and industrial activities within the metropolitan complex, decline of the central cities and emergence of suburban lifestyles, and the core question of community integration itself. Volume 8 includes case studies from Toronto, Japan, Bulgaria, and other geographic locations with ethnic minority populations. It addresses the major concepts of urban sociology while including perspectives from diverse locations.
Introduction : ethnic landscapes in an urban world / Ray Hutchison and Jerome Krase -- The earth's inhabitants scattered : the relationship between ethnicity and diaspora / Shalva Weil -- Diasporic globalization : reframing the local/global question / Michel S. Laguerre -- Multicultural and multiethnic cities in Australia / Vince Marotta -- Migration, new urban ethnic minorities and the race/ethnic relations approach in a recent immigration country : the case of Italy / Natalia Magnani -- Immigrant global neighbourhoods : perspectives from Italy and the United States / Jerome Krase and Tarry Hum -- Scarred and exiled : race and the Caribbean immigrant in Toronto 1970-2004 / Jerome Teelucksingh -- Spatial segregation and attachment to place : the case of immigrants from the FSU in Israel / Gustavo S. Mesch -- Aymara migrants in El Alto, Bolivia : a photographic essay / Jerome Crowder -- Koreans in Japan : urban settings and immigrant labor / David Rands -- Expatriate ethnoscapes: transnational masculinity and sexual transgressions / William H. Leggett -- Images of social inequality in a Bulgarian transition city : the market and the cemetery / Svetlana Hristova.
Includes bibliographical references.
Description based on print version record.
Keywords: Sociology, Urban; Immigrants -- Social conditions; Ethnicity; Ethnic studies; Urban communities; Social Science -- Sociology -- General